Role of Breastfeeding and Complementary Food on Hemoglobin and Ferritin Levels in a Cambodian Cross-Sectional Sample of Children Aged 3 to 24 Months. - Anika Reinbott; Irmgard Jordan; Johannes Herrmann; Judith Kuchenbecker; Ou Kevanna; Michael B Krawinkel (PLoS ONE)
Background Iron deficiency derives from a low intake of dietary iron, poor absorption of iron, and high requirements due to growth as well as blood loss. An estimated number of about 50% of all anemia may be attributed to iron deficiency among young children in Cambodia. Methods A cross-sectional survey was conducted in rural Cambodia in September 2012. Villages in pre-selected communes were randomly chosen using stunting as a primary indicator of nutritional status. In total, 928 randomly selected households with children aged 3-23 months were included. Hemoglobin, ferritin, soluble transferrin receptor (sTfR), and retinol binding protein (RBP) were assessed from capillary blood samples. In addition, length/height and weight of mothers and children were taken and data on dietary diversity was collected. A child feeding index (CFI) was created. Associations between biomarkers of iron and vitamin A status and nutritional status or food intake were explored. Results Anemia prevalence was highest among 6- to 12-months-olds (71%). Ferritin and sTfR inversely correlated and were significantly associated with hemoglobin concentrations. The consumption of animal source foods (ASF) significantly impacts on the interaction between ferritin, sTfR and hemoglobin. Concentrations of RBP were significantly higher in children who had received a vitamin A supplement. The CFI was associated with sTfR and hemoglobin. Lower length and weight were associated with lower ferritin levels and showed an indirect effect on hemoglobin through ferritin. Conclusion Nutrition programs targeting children under 2 years of age need to focus on the preparation of complementary foods with high nutrient density to sustainably prevent micronutrient deficiency and generally improve nutritional status. Future assessments of the micronutrient status should include identification of hemoglobinopathies and parasitic infections to better understand all causes of anemia in Cambodian infants and young children. Trial registration German Clinical Trials Register DRKS00004379.